Integration of Farming-Livestock Systems in Sustainable Agrocomplex Development in Indonesia - Nengsi, Sri Wahyu (Professorline, 2025)
Integrated farming-livestock systems offer a sustainable approach to agrocomplex development in Indonesia. This study analyzes the application of integrated systems in three different agroecosystems: wetlands in Karawang, drylands in Gunung Kidul, and plantations in Central Lampung. Research methods include direct observation, field measurements, and data analysis using Systems Dynamics Modeling, Data Envelopment Analysis, and Structural Equation Modeling. The results show three main typologies of integration: rice-cattle, food crops-horticulture-goats, and oil palm-livestock systems. Integrated systems increase nitrogen use efficiency by 37-52%, reduce chemical fertilizer needs by 45%, and increase farmer income by 43.7 % compared to conventional practices. Environmentally, these systems increase soil organic matter content, reduce greenhouse gas emissions by 2.4-3.7 tons CO₂-eq/ha/year, and increase biodiversity. Implementation challenges include institutional fragmentation, limited post-harvest technology, and lack of standardization of organic fertilizer quality. Critical success factors include institutional support, farmers’ technical capacity, and the suitability of technology to the local context. This research contributes to the development of a sustainable agrocomplex model that is adaptive to the diverse conditions of Indonesia’s agroecosystems, with important implications for food security and climate change mitigation policies.